2021
DOI: 10.1007/s10265-021-01273-9
|View full text |Cite
|
Sign up to set email alerts
|

In the tripartite combination Botrytis cinerea–Arabidopsis–Eurydema oleracea, the fungal pathogen alters the plant–insect interaction via jasmonic acid signalling activation and inducible plant-emitted volatiles

Abstract: In ecosystems, plants are continuously challenged by combined stress conditions more than by a single biotic or abiotic factor. Consequently, in recent years studies on plant relationships with multiple stresses have aroused increasing interest. Here, the impact of inoculation with fungal pathogens with different lifestyles on Arabidopsis plants response to the following infestation with the invasive crop pest Eurydema oleracea was investigated. In particular, as fungal pathogens the necrotroph Botrytis cinere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that one premise for pathogens and insects to choose cooperative or non-cooperative relationships is the order in which they infect host plants ( Meng, 2013 ). When a pathogen first infects a plant, it will induce the plant to produce volatile substances to avoid insect attack ( Ederli et al, 2021 ), and synergistic interactions between pathogens and insects have been utilized as a classical approach to the biological control of weeds ( Willsey et al, 2017 ). However, when insects first attack, they often do not adversely affect the pathogens that subsequently infect, and make the host even more conducive to infection by pathogens ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that one premise for pathogens and insects to choose cooperative or non-cooperative relationships is the order in which they infect host plants ( Meng, 2013 ). When a pathogen first infects a plant, it will induce the plant to produce volatile substances to avoid insect attack ( Ederli et al, 2021 ), and synergistic interactions between pathogens and insects have been utilized as a classical approach to the biological control of weeds ( Willsey et al, 2017 ). However, when insects first attack, they often do not adversely affect the pathogens that subsequently infect, and make the host even more conducive to infection by pathogens ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as reported in the interactions between other hosts and Botrytis spp. (e.g., Arabidopsis – B. cinerea and Arabidopsis – Alternaria brassicicola ), the SA and JA signaling pathways play a crucial role in the response of “Sorbonne” to fungal infection (Zheng et al, 2006 ; Ederli et al, 2015 , 2021 ; Liao et al, 2020 ). Besides, the BR-related genes were significantly up-regulated during across all infection stages in our results.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR programme for PDF 1.2 was as reported in Ederli et al . ( 2021 ) with slight modifications. Briefly, it consisted of 94 °C for 1 min 15 s, 32 cycles of 5 s at 94 °C, 20 s at 57.5 °C and 45 s at 72 °C, followed by 6 min at 72 °C.…”
Section: Methodsmentioning
confidence: 99%